What works? Academic integrity and the research-policy relationship. Issue 6 (17th August 2020) - Gewirtz, Sharon; Cribb, Alan
Abstract: In this paper, we consider the intensifying pressures on critical research and academic integrity in a research policy context that has come to be increasingly dominated by an instrumentalist mind-set. Using sensitising resources drawn from Geoff Whitty's critique of the 'what works' agenda, we reflect on the current conditions of academic labour and some of the key issues and dilemmas they pose for critical researchers in the sociology of education and beyond. In particular, we underline the trend for 'what works' agendas to become constitutive of academic identities and practices, including at micro-levels, such that the option of 'standing outside' them is shifting from being merely personally taxing to being institutionally disallowed. In addition to highlighting the dilemmas this creates for critical researchers and the threat this poses to expansive and democratic approaches to education, the paper emphasises the centrality of relationship-forming in understanding and underpinning academic integrity.